PERSEPSI BODY IMAGE DENGAN KEBIASAAN JAJAN MAHASISWA UNIVERSITAS NEGERI SURABAYA (KAMPUS KETINTANG) - Nila Anggita Nur Faizah; Amalia Ruhana (Jurnal Sehat Mandiri, 2021)
Body image is the subjective imagination of a person regarding the judgments of other on his body. The ideal body image can encourage someone to do things such as physical changes and other changes, namely snack consumption patterns. This is often experienced by students. This study aims to determine the relationship between perceptions of body image and snacking habits in students. The research targets were Universitas Negeri Surabaya students who were on the Ketintang campus with a sample of 100 people who had met the inclusion criteria. This study used an observational analytical study design with a cross-sectional approach. The instruments used in this study are Body Shape Questionnaire and interviews using a semi-quantitative Food Frequency Questionnaire. The result is 56% of respondents’ body image perceptions negative and 70% of respondents admit to snacking frequently. The resuts of the correlation test showed that there was no relationship between perception of body image and the respondent’s eating habits (p > 0,05). It can be concluded that most respondents are not satisfied with their body image, even though the majority of them often consume snacks every day. It is suggested that students need to get good nutrition education and learning related to body image perception in order to have a positive body image perception. Further research is needed to determine other factors that can affect the perception of body image in students.